Anti-inflammatory effect of a pimarane diterpenoid isolated from Nepeta adenophyta Hedge based on a network analysis approach and experimental assessment - Zhao, Wei; Li, Meng; Jia, Chuanqing; Ali, Iftikhar; Chen, Long (Frontiers in Pharmacology, 2025)
BackgroundAs an important folk medicine in Pakistan, Nepeta adenophyta Hedge has been widely used to treat abdominal pain, kidney pain, headaches, and for the alleviation of dysmenorrhea. The pimarane-type diterpenoids are known for their anti-inflammatory activity, but their mechanistic pathways remain understudied. 2,4b,8,8-Tetramethyl-2-vinyl-1,2,3,4,4a,4b,5,6,7,8,8a,9-dodecahydro-phenanthrene-3,5-diol (1), a pimarane diterpenoid, was detected primarily from N. adenophyta Hedge through its gas chromatography-mass spectrometry (GC-MS) fragmentation pathways. The GC-MS-guided isolation yielded compound 1 (NAC, N. adenophyta compound) in pure form.MethodsThe GC-MS guided isolation of compound 1 was performed by column chromatography on normal silica gel. The structure was characterized by spectroscopic techniques. Then, the potential targets, pathways, and hub genes for treating inflammatory diseases were screened out through network analysis, and core targets were docked with 1 via docking software. Based on the results of network analysis, an MTT assay was performed to determine cell proliferation in the RAW264.7 cell line. Inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and prostaglandin E2 (PGE2), were tested by enzyme-linked immunosorbent assay (ELISA). Immunofluorescence and Western blot assays were used to verify the function of 1 in the treatment of inflammation.ResultsCompound 1 was isolated from N. adenophyta Hedge in its pure form. The pharmaceutical network results showed that it has a potential anti-inflammatory effect through the PPAR and NF-κB signaling pathways. The ELISA results showed that 1 could attenuate the content of pro-inflammatory cytokines. Additionally, the translocation of NF-κB p65 into the nucleus was significantly decreased in the immunofluorescence method. The Western blot analysis results showed that 1 significantly inhibited the protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Furthermore, it decreased the phosphorylation of nuclear factor kappa B inhibitor α (IκBα) and toll-like receptor 4 (TLR4) by the NF-κB signaling pathway. Compound 1 also reduced reactive oxygen species (ROS) levels and restored overexpressed heme oxygenase-1 (HO-1) and serine/threonine kinase (AKT) to the basal level.ConclusionThe present study indicates that compound 1 shows a significant anti-inflammatory effect, potentially through intervention in the NF-κB and PPARγ signaling pathways.